Rusya Federasyonu’Nda İş Güvenliğinin Gelişimi, İnşaat Sektöründe İş Güvenliği Mevzuatı - Sancak, Liliya (Fen Bilimleri Enstitüsü)
Bu tez çalışmasında Rusya Federasyonu’ndaki İş Güvenliği Mevzuatı araştırılmış ve araştırma sonucu edinilen bilgiler; Rusya’da faaliyet gösterecek olan Türk inşaat firmalarına bir rehber niteliğinde sunulmuştur. Bu araştırma yapılırken iş güvenliği kavramının; ülkenin tarihsel dönüm noktalarına göre; Rusya İmparatorluğu döneminde, sonrasında Sovyet Sosyalist Cumhuriyetler Birliği döneminde ve bugünkü Rusya şartlarında gelişimi ve uğradığı değişimler hakkında bilgi verilmiştir. Araştırmada Rusya’nın inşaat sektöründeki iş güvenliği mevzuatı ele alınarak konunun en önemli dokümanları bir araya getirilmiştir. İnşaat projelerinin, uygulamada olmazsa olmazları niteliğindeki iş güvenliği eğitimi, iş kazalarının incelenme süreci, çalışma yeri şartları denetimi, devlet denetimi ve şirketin iç denetimleri başlıklarının dikkat edilmesi gereken hususları irdelenmiştir. Büyük bir Türk inşaat şirketinin Rusya’daki iş güvenliği mevzuatının gerektirdiği uygulamada örnek olabilecek dökümantasyon paketi incelenmiş ve Türk inşaat firmalarına olumlu katkısı olabileceği düşüncesiyle bu dokümantasyon üzerinden değerlendirmeler yapılmıştır.

In this thesis the Occupational Safety Legislation in Russian Federation has been researched and obtained informations presented as a tutorial for Turkish construction companies which will operate in Russia. In this study, informations have been provided about the development and enduring significant changes of occupational safety term while the concept of the country s historical turning points, according to the period of Russian Empire, after the Union of Soviet Socialist Republics period and under the conditions of today s Russia. The Russian construction industry occupational safety legislation have been investigated and the most important documents of this subject have been gathered in this study. The important points of the sie qua non subjects of construction projects in implementation phase like occupational safety training, inspections of workplace hazards, the sertification of workplaces, government audit and public internal audit have been examined In conclusion of study, the occupational safety documentation package of large-scale Turkish construction company which could be an instance for Turkish contractors in Russia have been analysed and the assessments have been made over this document with the idea of making a positive contribution to construction companies’ activities.
The development of occupational safety in Russian Federation and occupational safety legislation in construction sector
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2013
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2013
Keywords: Rusya Federasyonu; İş güvenliği; Mevzuat; Müteahhit; Russian Federation; Occupational health and safety; Legislation; Contractor